Common Auditors and Private Bank Loans* - Francis, Jere R.; Wang, Wei (Contemporary Accounting Research, 2021)
ABSTRACT We show that when banks and borrowers share the same audit firm, borrowers receive lower interest rates, after controlling for potentially confounding director connectedness. The common auditor effect is observed only for opaque borrowers, and is greatest when the same audit engagement office audits the bank and borrower. A common auditor connection also matters more for longer‐tenured auditors, for geographically proximate borrowers, and when the syndicate involves fewer lenders. The effect does not hold for auditors recently sanctioned by the PCAOB. Finally, the interest rate discount is not the consequence of homophily or biased decision making, based on a comparison of postloan performance of firms with common auditor loans versus those with noncommon auditor loans.